Nerve growth factor suppresses the transforming phenotype of human prolactinomas. - Missale, C (1993)
The most effective therapy of human prolactinomas is represented by dopamine D-2 receptor agonists; there is, however, a population of nonresponder patients who require surgical intervention. In the present study, we report that prolactinomas totally resistant to pharmacological therapy have a high potential of both growing in soft agar and forming tumors in nude mice and lack D-2 receptors for dopamine. These tumors express the receptors for nerve growth factor (NGF) and are sensitive to its differentiating activity. After exposure to NGF for 4 days, prolactinoma cells decreased their proliferation rate, lost their capability to form colonies in soft agar, lost their tumorigenic activity in nude mice, and reexpressed the lactotroph-specific D-2 receptor protein inhibiting prolactin release. These effects were permanent after NGF withdrawal and were reproducible in vivo in nude mice transplanted with the tumors. NGF in fact remarkably and lastingly depressed tumor growth and induced expression of D-2 receptors when injected intravenously once a day for 5 days into prolactinoma-bearing nude mice. These data suggest that NGF may induce a long-lasting switch of gene expression in human prolactinomas, modifying their transforming phenotype and reverting them to more differentiated, less malignant, dopamine-sensitive lactotroph-like cells. The possibility thus arises that short-term treatment with NGF may restore the refractory patients to conventional pharmacological therapy with D-2 agonists.